Cyclooxygenase-2/prostaglandin E2 inhibition remodulated photodynamic therapy-associated immunosuppression for enhanced cancer immunotherapy - Tao Xu; Kehan Liu; Shuqi Mi; Yao Yao; Mengyao Zhang; Shujuan Xue; Feng Zhi; Sally-Ann Cryan; Dawei Ding (Materials Today Bio)
Low immunogenicity and immunosuppressive tumor microenvironment (TME) are two pivotal factors restricting tumor immunotherapy. Photodynamic therapy (PDT) directly destroys cancer cells by producing reactive oxygen species (ROS), and enhances the immunogenicity of ''cold'' tumors by inducing immunogenic cell death (ICD), thereby promoting T cell development against tumors. However, PDT also deteriorates immunosuppression through overactivating the cyclooxygenase-2/prostaglandin E2 (COX-2/PGE2) pathway. To this end, biocompatible albumin nanoassemblies co-delivering IR780 and diclofenac are herein developed for enhanced therapy against triple-negative breast cancer. PDT-exacerbated PGE2 overexpression is effectively abolished by diclofenac-mediated COX-2 inhibition, which reprograms immunosuppressive TME via downregulating the infiltration of various immunosuppressive cells and their cytokine secretion to enhance effector T cell infiltration. Consequently, the enhanced antitumor immunity effectively inhibits tumor growth, prevents the recurrency and metastasis, and remarkably boosts the treatment efficacy of PD-L1 blockade. This study sets an intriguing example for overcoming the COX-2/PGE2 pathway-exacerbated immunosuppression alongside immune activation, thus enhancing synergistic cancer immunotherapy potentiated by various ROS-producing therapies (e.g., PDT and radiotherapy) and chemotherapy.